"PUNCTUATION IN LINGUISTICS: TRADITIONAL AND MODERN APPROACHES" - Turaeva Dilbar Meylievna (Western European Studies, 2024)
Punctuation is the tool that allows us to organize our thoughts and make it easier to review and share our ideas. Punctuation, the use of spacing, conventional signs, and certain typographical devices as aids to the understanding and correct reading, both silently and aloud, of handwritten and printed texts. The punctuation now used with English and other western European languages is derived ultimately from the punctuation used with Greek and Latin during the classical period. Much work remains to be done on the history of the subject, but the outlines are clear enough.
Keywords: linguistics; spelling; writing